Sistem Pembinaan Perilaku Bullying Santri Pondok Pesantren Puncak Darussalam Pamekasan Berbasis Pencatatan Digital - Adit Asrori; Abdul Wahid (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2026)
Bullying is a form of violence that has serious impacts on the psychological, social, and academic development of students, including in pesantren environments that are characterized by intensive interaction patterns and hierarchical social structures. This study aims to analyze the forms of bullying behavior among santri and to examine the implementation of a digital record–based bullying behavior guidance system at Pondok Pesantren Puncak Darussalam Pamekasan through the CBU (Character Building and Ubudiyah) system. The study employs an embedded mixed-methods approach with qualitative dominance and a case study design. Data were collected through in-depth interviews, observation, documentation, and analysis of digital records of santri behavior. The findings indicate that bullying behavior in the pesantren manifests in verbal and physical forms. The implementation of the CBU digital recording system plays an important role in systematically mapping the forms and frequency of bullying behavior, while also serving as a foundation for more focused character development programs. Character development is carried out through humanistic and educational approaches, including dormitory visits, character education studies, and the internalization of Islamic values such as rahmatan lil-‘alamin, honesty, guarding one’s speech, and refraining from harming others. This study concludes that digital record–based guidance systems should be integrated with value-based education and exemplary practices to strengthen social control and character formation of santri within the pesantren environment. Keywords: santri bullying, pesantren, digital recording, character building, CBU.